2021
DOI: 10.3389/froh.2020.603160
|View full text |Cite
|
Sign up to set email alerts
|

Major Molecular Signaling Pathways in Oral Cancer Associated With Therapeutic Resistance

Abstract: Oral cancer is a sub-category of head and neck cancers that primarily initiates in the oral cavity. The primary treatment option for oral cancer remains surgery but it is associated with massive disfigurement, inability to carry out normal oral functions, psycho-social stress and exhaustive rehabilitation. Other treatment options such as chemotherapy and radiotherapy have their own limitations in terms of toxicity, intolerance and therapeutic resistance. Immunological treatments to enhance the body's ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 180 publications
(214 reference statements)
0
26
0
Order By: Relevance
“…Cancer stem cells (CSC) are a small population of cells capable of self-renewal, which are known to resist therapeutic interventions and immune responses. Being pluripotent, these cells can provide cellular seeds to initiate new tumours at distant sites [ 23 ]. It was proposed that EMT can transform non-CSCs into cancer stem cells, which are invariably vimentin-positive [ 24 ].…”
Section: Emt May Produce Cancer Stem Cells (Cscs) Expressing Vimentinmentioning
confidence: 99%
“…Cancer stem cells (CSC) are a small population of cells capable of self-renewal, which are known to resist therapeutic interventions and immune responses. Being pluripotent, these cells can provide cellular seeds to initiate new tumours at distant sites [ 23 ]. It was proposed that EMT can transform non-CSCs into cancer stem cells, which are invariably vimentin-positive [ 24 ].…”
Section: Emt May Produce Cancer Stem Cells (Cscs) Expressing Vimentinmentioning
confidence: 99%
“…Thus, one single strategy might not be sufficient, and increased insights to the resistance mechanisms as well as identification of biomarkers will help to design novel and optimized therapeutic strategies, which either direct against tumor cells and/or modulate tumor microenvironment. These issues are also discussed in several recent excellent reviews [ 3 , 137 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a molecular switch, activated K-RAS is vital for stimulating the downstream signaling cascade via the Raf/MEK/ERK and PI3K/AKT/mTOR pathways after extracellular ligands, such as EGF, bind to the membrane receptor [ 39 ]. In OSCC patients, K-RAS frequently mutates into H-RAS, although the reason for this is unknown (this mutation is frequently detected in smokers and betel quid-chewing individuals [ 40 ]). Previous studies have demonstrated that the H-RAS mutation plays a crucial role in treatment failure and the development of resistance to cetuximab in OSCC, by stimulating downstream genes like c-MYC, BCL-XL, and BCL-2 [ 41 ].…”
Section: Cetuximab: a Mab And Egfr Inhibitormentioning
confidence: 99%